Peran Guru dalam Membentuk Karakter Disiplin Siswa melalui Kegiatan Rutin 3S (Senyum, Salam, Sapa) di SDN Padike III Talango Sumenep - Dhini Savira Ramadhani; Iwan Kuswandi; Agus Wahdian (Universitas Palan, 2026)
Character education is an inseparable part of the educational process, especially at the elementary school level. One of the efforts undertaken by SDN Padike III Talango to foster students’ discipline is through the implementation of the daily 3S routine (smile, greet, salute). This study aims to describe the role of teachers in carrying out the 3S activities, identify supporting and inhibiting factors, and formulate strategies to ensure the program runs consistently and sustainably. The method used is qualitative research with data collection techniques including participatory observation, in-depth interviews, and documentation. The results indicate that teachers serve as role models, motivators, facilitators, as well as activity managers who actively encourage the development of discipline among students. The regular implementation of 3S has proven effective in creating a friendlier, more orderly, and more conducive school environment, and it contributes to reducing conflicts among students. Supporting factor for the program’s success include exemplary leadership from the principal and teachers, consistent implementation, and parental involvement. Barriers encountered include inconsistency among some students, external environmental influences, and the diverse backgrounds of families. The daily 3S routine can be an effective strategy for instilling students’ disciplinary character when implemented consistently and supported by all school members as well as parents.